2001
DOI: 10.1603/0022-0493-94.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Insecticide Residues on <I>Orius insidiosus</I> (Hemiptera: Anthocoridae) and <I>Geocoris punctipes</I> (Hemiptera: Lygaeidae)

Abstract: Laboratory-reared predators, the insidious flower bug, Orius insidiosus (Say), and big-eyed bug Geocoris punctipes (Say), were exposed to 10 insecticides, including three newer insecticides with novel modes of action, using a residual insecticide bioassay. These species are important predators of several economic pests of cotton. Insecticides tested were: azinphos-methyl, imidacloprid, spinosad, tebufenozide, fipronil, endosulfan, chlorfenapyr, cyfluthrin, profenofos, and malathion. There was considerable vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 12 publications
6
63
0
3
Order By: Relevance
“…Unfortunately, to date pymetrozine and imidicloprid are not available to soybean growers in a form that can be applied to soybean foliage. One product that includes imidicloprid (Leverage, Bayer CropScience) is available to farmers; however, this product also contains cyßuthrin, a broad-spectrum insecticide that would probably remove existing natural enemies (Elzen 2001). Thus, the beneÞts from the use of reduced-risk insecticides, as it relates to pest management, may be at risk if these products are sold in combination with a broad-spectrum insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date pymetrozine and imidicloprid are not available to soybean growers in a form that can be applied to soybean foliage. One product that includes imidicloprid (Leverage, Bayer CropScience) is available to farmers; however, this product also contains cyßuthrin, a broad-spectrum insecticide that would probably remove existing natural enemies (Elzen 2001). Thus, the beneÞts from the use of reduced-risk insecticides, as it relates to pest management, may be at risk if these products are sold in combination with a broad-spectrum insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were isolated from the soil actinomycetes Saccharopolyspora spinosa [Kowalska and Drozdzyński, 2009]. Spinosad possesses both contact and stomach poison activity against insects belonging to Coleoptera, Diptera, Hymenoptera, Isoptera, Lepidoptera, Siphonoptera and Thysanoptera but has little or no activity against sucking insects, predatory insects and mites [Elzen, 2001;Galvan et a1., 2006;Elliot et al, 2007]. It is a neurotoxin with a novel mode of action involving the nicotinic acetylcholine receptor and apparently the GABA receptors as well [Cisneros et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used against crop pests (Nauen et al 1998, Elzen 2001, Capowiez & Berard 2006, but Paul et al (2006) recently found that it was also effective against both the larvae and adult stages of Ae. aegypti.…”
mentioning
confidence: 99%